THE NAVIER-STOKES-CONTINUITY EQUATION SOLVER BASED ON ARTIFICIAL COMPRESSIBILITY METHOD - Bahrul Jalaali (Institut Teknologi Dirgantara Adisutjipto, 2020)
Fluid dynamics analysis can be accurately approximated by using a computer-based numerical method. Rely on the mass and momentum governing equation, the mathematics model for the compressible condition is numerically difficult to overcome. Through an artificial compressibility method, the quasi-compressible condition solution can be simplified. This study will investigate the classical lid-driven cavity case model to affirm the artificial compressibility method. The result shows that the current model is in-line with the previous study for the lid-driven cavity case. A conventional benchmark with the previous numerical study is shown as well.